ARTHROPOD EMERGENCE ON LAND - SHARMA DURGVIJAY ANIRUDH (International Journal of Multidisciplinary Research and Studies, 2020)
Longleaf pine (Pinus palustris Mill.) savannas are characteristic of the lower coastal plains of the southeastern United States. These savannas, once a ubiquitous part of the landscape, have become a severely diminished and endangered ecosystem. Prior to European settlement, this ecosystem historically extended from Virginia, south to Florida, and west to Texas (Barnett 2013) and spanned approximately 37 million hectares (Aschenbach et al. 2010; Frost 1993). Now, only 1.3 million hectares remain and the land that does remain is often patchy and degraded in large part due to human- mediated changes in historic fire regimes (Barnett 2013; Aschenbach et al. 2010; Gilliam & Platt 1999). European colonization of the U.S. led to rapid and dramatic change and/or reduction in native ecosystems. In the Southeastern U.S., declines in longleaf pine savannas, have been so steep that they have become one of the most endangered ecosystems in the country (Aschenbach et al. 2010). Approximately 97% of this ecosystem has been decimated by logging, conversion to agricultural lands, urbanization, and fire suppression (Barnett 2013; Aschenbach et al. 2010).